2010
DOI: 10.1021/bm1008712
|View full text |Cite
|
Sign up to set email alerts
|

A-Type Crystals from Dilute Solutions of Short Amylose Chains

Abstract: Model A-type amylose single crystals were prepared by recrystallizing dextrins from acid-hydrolyzed native starch and narrow fractions of short chains of enzymatically synthesized amylose, in dilute water/acetone solutions. In most cases, spindle-shaped crystals with a sharp, round or flat apical end were formed, organized in rosettes or fan-like assemblies. The morphology and crystal size were shown to strongly depend on the average degree of polymerization (DP), distribution width (DW), and degree of branchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 42 publications
0
37
1
Order By: Relevance
“…The B-type crystallites may form temporarily, but this structure may rearrange to form the more stable Atype structure. A general rule is that A-type crystallites are favored at high temperatures, short average chains, higher concentrations, and presence of salts, water-soluble alcohols, organic acids (Gidley, 1987;Montesanti et al, 2010). Gidley and Bulpin (1989) found that re-crystallization and gelation behavior of amylose in aqueous solution (0.2e5.0 %) show a dependence on chain length (synthesized in vitro using potato phosphorylase, degree of polymerization (DP) ranging from 40 to 2800).…”
Section: Ers From Densely Packed Matrices: Mechanisms and Categoriesmentioning
confidence: 99%
“…The B-type crystallites may form temporarily, but this structure may rearrange to form the more stable Atype structure. A general rule is that A-type crystallites are favored at high temperatures, short average chains, higher concentrations, and presence of salts, water-soluble alcohols, organic acids (Gidley, 1987;Montesanti et al, 2010). Gidley and Bulpin (1989) found that re-crystallization and gelation behavior of amylose in aqueous solution (0.2e5.0 %) show a dependence on chain length (synthesized in vitro using potato phosphorylase, degree of polymerization (DP) ranging from 40 to 2800).…”
Section: Ers From Densely Packed Matrices: Mechanisms and Categoriesmentioning
confidence: 99%
“…Recently, many researchers have reported various properties of amylose such as structural conformation and stability in solvents (Nakanishi et al 1993;Shimada et al 2000;Radosta et al 2001;Tusch et al 2011), conformational transitions (Cheetham & Tao 1997), crystallisation and crystal structure (Takahashi et al 2004;Creek et al 2006;Popov et al 2009;Montesanti et al 2010), amylose complexes (Hulleman et al 1996;Ozcan & Jackson 2002;Nuessli et al 2003;Ciesielski & Tomasik 2004;Cardoso et al 2007;Nishiyama et al 2010), gel microstructure and textural properties (Torres et al 1978;Leloup et al 1992) and amylose gel physical network (Lay & Delmas 1998). Whereas, research on the properties of amylopectin was focused on its structural and retrogradation properties (Manners & Matheson 1981;Manners 1989;Paredes-Lopez et al 1994), crystallinity of amylopectin films and network formation (Putaux et al 2000;Myllarinen et al 2002), and amylopectin complexes (Ciesielski & Tomasik 2004).…”
mentioning
confidence: 99%
“…In the case of B‐type amylose crystallite, the strongest diffraction peak at around 17° 2 θ , a few small peaks at around 15°, 20°, 22°, and 24° 2 θ , and a characteristic peak at about 5.6° 2 θ are observed . Low crystallization temperature generally favors the B form .…”
Section: Resultsmentioning
confidence: 96%
“…Amylose crystallite is known to be constructed from double‐stranded helices . Potato amylose contains negatively charged phosphate groups .…”
Section: Resultsmentioning
confidence: 99%